2008
DOI: 10.1097/qad.0b013e32830e0152
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hepatitis C virus coinfection on HIV-related kidney disease: a systematic review and meta-analysis

Abstract: In the era of antiretroviral therapy, non-AIDS complications such as kidney disease are important contributors to morbidity and mortality. Objective To estimate the impact of hepatitis C co-infection on the risk of kidney disease in HIV patients. Design/ Methods Two investigators identified English-language citations in MEDLINE and Web of Science from 1989 through July 1, 2007. References of selected articles were reviewed. Observational studies and clinical trials of HIV-related kidney disease and antiretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 56 publications
3
84
1
8
Order By: Relevance
“…In a study of 202 Hispanic HIV-infected and -uninfected drug users, the prevalence of proteinuria was only 10.9% (14). A meta-analysis of HIV/ HCV co-infected populations, to which our HIV-infected participants should be similar, suggested a pooled estimate of CKD prevalence of 28% (15), which is 21% lower than the estimate among our HIV/HCV co-infected participants. The heavier burden of proteinuria in our population may collectively reflect the predominance of African-American participants in our study and the high prevalence of HIV, HCV, and HIV/HCV co-infection.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In a study of 202 Hispanic HIV-infected and -uninfected drug users, the prevalence of proteinuria was only 10.9% (14). A meta-analysis of HIV/ HCV co-infected populations, to which our HIV-infected participants should be similar, suggested a pooled estimate of CKD prevalence of 28% (15), which is 21% lower than the estimate among our HIV/HCV co-infected participants. The heavier burden of proteinuria in our population may collectively reflect the predominance of African-American participants in our study and the high prevalence of HIV, HCV, and HIV/HCV co-infection.…”
Section: Discussioncontrasting
confidence: 58%
“…Although we did not observe an association between African-American race and proteinuria, this may reflect the small sample size of Caucasians, and the overall high prevalence of proteinuria in this cohort may at least in part reflect the predominance of African Americans. In previous studies, which drew from this and similar populations, strong associations were observed between African-American race and development of ESRD, and survival rates after dialysis initiation were poor (15,27). Early diagnosis and care for CKD may help to prevent more serious kidney damage, eventual kidney failure, and the need for dialysis.…”
Section: Discussionmentioning
confidence: 73%
“…Thirty-eight observational studies were considered eligible but were excluded because outcomes from HCV-HIV co-infected participants (n=32) (15), patients with diabetes (n=2) (16,17), HCV-infected patients (n=1) (18), and chronic GN patients only (n=1) (19) were reported. Two studies did not account for important potential confounders in their analyses (20,21).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the authors commented that few of the studies provided a clear definition of HCV coinfection, and only one required HCV RNA testing for diagnosis. 8 Thus, additional investigation is needed to understand the mechanisms underlying the association between HIV/HCV coinfection and renal disease.…”
mentioning
confidence: 99%